If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3(x + -4) = 3x + -6 Reorder the terms: 8x + -3(-4 + x) = 3x + -6 8x + (-4 * -3 + x * -3) = 3x + -6 8x + (12 + -3x) = 3x + -6 Reorder the terms: 12 + 8x + -3x = 3x + -6 Combine like terms: 8x + -3x = 5x 12 + 5x = 3x + -6 Reorder the terms: 12 + 5x = -6 + 3x Solving 12 + 5x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 5x + -3x = -6 + 3x + -3x Combine like terms: 5x + -3x = 2x 12 + 2x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + 2x = -6 + 0 12 + 2x = -6 Add '-12' to each side of the equation. 12 + -12 + 2x = -6 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = -6 + -12 2x = -6 + -12 Combine like terms: -6 + -12 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| .4h+1=16-1.1h | | 4t-1=-13 | | -7-7k=-21 | | -3n-1=-13 | | 2+2w=-18 | | 3d-4=-22 | | 7a+10=38 | | 5k+10=30 | | 4w+10=46 | | 1+6w=7 | | 3+7a=3 | | 6w-4=68 | | 4d+5=21 | | 8+5b=68 | | 3m+3=39 | | -2a+3=-13 | | 5d+5=10 | | 6n+8=68 | | -7d-5=-89 | | -7d+1=-27 | | 6m+1=55 | | 0.04p-0.05=0.03p+0.011 | | 5+3k=20 | | 84+(-99)+44-(-18)-43= | | 10-6w=-2 | | 5k+8=-27 | | 7-7k=42 | | -7m+8=-41 | | 6-3k=-3 | | 4+7x=-17 | | y-13=-7 | | -7b-7=-21 |